EKSTERNALITAS PABRIK KELAPA SAWIT DI ACEH TAMIANG - Ichsan Sandi; Taufq C. Dawood (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2019)
Abstract Aceh is one of the provinces in indonesia where most of the people work as farmers. Aceh tamiang, is of the districts in the province of aceh that has extensive oil palm mills to meet economic needs. This study aims to determine the externality of palm oil mills in aceh tamiang. This research  method uses qualitative analysis using the big formula, n≥30. The data uses in the study are primary data by distributting questionnaires to 33 respondents using the snowball sampling technique. The result of the analysis of this study indicate that labor can reduce the unemployment rate of the surrounding community and can improve the welfare of the community around the palm oil mill. The income of the residents around the palm oil mill also increases, which will affect the level of consumption. New business actor also influence the existence of palm oil mills. Existence of PT. Padang Palma Permai in Aceh Tamiang has a positive impact on the variables of labor, income, and new business actors.Keywords: Labor, Revenue, Business Actor